Research on Control of Rib Spalling Disaster in the Three-Soft Coal Seam - Feng Cui; Tinghui Zhang; Xiaoqiang Cheng (Shock and Vibration)
Rib spalling disaster at the coal mining faces severely restricted the safe and efficient output of coal resources. In order to solve this problem, based on the analysis of the current status of rib spalling in the three-soft coal seam 1508 Working Face of Heyang Coal Mine, a mechanical model of sliding-type rib spalling was established and the main influencing factors that affect rib spalling are given. The mechanism of grouting technology to prevent and control rib spalling has been theoretically analyzed. A similarity simulation experiment is used to analyze the change law of roof stress under the condition of three-soft coal seam mining. The optimal grouting pressure is determined by a numerical simulation experiment. And, silicate-modified polymer grouting reinforcement materials (SMPGMs) are used in field experiments. After twice grouting operations in the 1508 Working Face, the coal wall was changed from the original soft and extremely easy rib spalling to a straight coal wall and the amount of rib spalling has been reduced by 57.45% and 48.43, respectively. And, the mining height has increased by 0.16 m and 0.23 m, respectively. The experimental results show that the rib spalling disaster of the three-soft coal seam has been effectively controlled.